Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Alfamart Ruko Cempaka Mas - Della Apriliani; Suhardoyo Suhardoyo; Lela Elvira (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
There are many other retail business competitors, such as Indomaret, where Alfamart must have superior product quality compared to Indomaret so that Alfamart Ruko Cempaka Mas will have more consumers. This research aims to determine the influence of price and product quality on purchasing decisions at Alfamart Ruko Cempaka Mas. The research method used is a quantitative research method with the research population being consumers who shop at Alfamart Ruko Cempaka Mas. The data analysis technique used is the multiple linear regression test. The results of this research show the influence of price on purchasing decisions, namely thituing (5,231) > ttabeil (2,010). there is an influence of product quality on purchasing decisions, namely thituing (3.051) > ttabeil (2.010). Price and product quality simultaneously have a significant influence on purchasing decisions with a value of Fhituing (14,315) > Ftabeil (4,038). In the test results, the coefficient of determination R Square value is 0.374 or 37.4% of purchasing decisions are influenced by price and product quality variables, while the remaining 62.6% is influenced by other factors.